Study guide for Gravetter and Wallnau's Statistics for the behavioral sciences - Gravetter, Frederick J (Thomson/Wadsworth, 2007)
It is really a good book but at times, the language gets too complicated even for a graduate student. The book comes with instructor slides (that my instructor did provide) which made the reading of this book a lot more understandable